202k views
2 votes
Solve for x: −2(x + 3) = −2x − 6 NEED HELP PLZ:(

A: 0
B: 3 C:All real numbers
D:No solution

2 Answers

4 votes

Answer:

C: All real numbers.

Explanation:

-2 ( x + 3 ) = -2x -6

-2 times x, -2 times 3

-2x -6 = -2x -6

Add 6

-2x -6 +6 = -2x -6 +6

-2x = -2x

same as....

0 = 0

User Piotr Krysiak
by
6.1k points
0 votes

Answer:

The answer is C:All real solutions

Explanation:

here are the steps in case u need them :)

Step 1: Simplify both sides of the equation.

−2(x+3)=−2x−6

(−2)(x)+(−2)(3)=−2x+−6(Distribute)

−2x+−6=−2x+−6

−2x−6=−2x−6

Step 2: Add 2x to both sides.

−2x−6+2x=−2x−6+2x

−6=−6

Step 3: Add 6 to both sides.

−6+6=−6+6

0=0

User Ray Li
by
5.4k points